Optimasi Proses Produksi Bakery Bakoel Ummi Aila Menggunakan Integer Programming Metode Branch And Bound (International Forum of Researchers and Lecturers, 2023)
CV XXX is one of the micro, small and medium enterprises (MSME) engaged in the food sector, namely bread making. In carrying out its business ventures, CV XXX has a problem, which is not knowing whether the benefits are really maximized or not. The purpose of this study was to find out the effective optimization of the production process and to compare the maximum profit obtained by CV XXX before and after implementing Integer programming using the Branch and Bound method. The data used in this study is primary data obtained from the results of interviews with the CV Langsung Enak Bakery. Based on the results of the study, it was found that in order to optimize the production process effectively in one production run, it is better for CV XXX to produce 76 packs of vanilla chocolate bread, 58 packs of chocolate bread, 66 packs of meses cheese bread, 6 packs of sliced combed bread, 52 packages of torn comb bread, and 614 boxes of white bread, and did not produce 2-flavor bread, 8-flavor bread, chocolate meses bread, round sweet bread, variety comb bread and plain white bread. The maximum profit earned is Rp. 3,024,378 with a total of 872 packaged products and an increase in profits of 13.3% from factual conditions.